Determination of selenium content in selected edible green leaves - D. S. M. De Silva (Ceylon Journal of Science, 2019)
The selenium (Se) contents in seven conventional Edible Green Leaves (EGL) that consumed by Sri Lankans were determined using Hydride Generation Atomic Absorption Spectrometric method (HGAAS). The EGLs that were grown in five districts under different climatic conditions in Sri Lanka were collected from Gampaha, Kandy, Kurunegala, Anuradhapura and Puttalam areas. The EGL that were subjected to current study are Centella asiatica (Sin. Gotukola), Alternanthra sessilis (Sin. Mukunuwenna), Basella alba (Sin. Nivithi/ Spinach), Boerhavia diffusa (Sin. Sarana), Ipomoea aquatica (Sin. Kankun), Amaranthus spinosus (Sin. Thampala) and Hygrophila schulli (Sin. Neeramulliya). Soil samples corresponding to each EGL sample were also collected from Gampaha, Kandy and Anuradhapura districts in order identify a relationship between the Se content in plants and soils. Prior to the analysis EGL samples and corresponding soil samples were subjected to acid digestion with nitric acid. Se contents in the EGL were in the range of 31.2 – 103.2 μg kg-1 on dry weight basis. According to the results, Centella asiatica and Hygrophila schulli varieties showed relatively higher Se content, while Hygrophila schulli shown the highest value and the lowest was reported in Boerhavia diffusa. The Se content in corresponding soil samples were ranged from 96.4 to 133.9 μg kg-1 on dry weight basis. The Se content in soil was higher than that in plants, but there was no significant correlation between the Se content in soil and EGLs.